2017
DOI: 10.1111/plb.12649
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of flower colouration in 30 Rhododendron species via anthocyanin and flavonol identification and quantitative traits

Abstract: Floral colour is a key reproductive character, often associated with environmental adaptation, and subject to human intervention. A large number of Rhododendron species differ widely in flower colour, providing a good model for flower colouration. The chromatic features and anthocyanin compositions of 30 species from seven subgenera were systematically analysed. The Royal Horticultural Society Colour Chart and CIE L*a*b* system were employed to describe and investigate flower colours. The UPLC-PDA/ESI-MS syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…However, the function was limited to flavonols, as a co-pigmentation, to change the petal color from magenta to blue color [34, 35]. Du et al (2018) reported the anthocyanin composition of 30 Rhododendron species and showed that there was no significant difference in co-pigmentation index among color different groups and flavonols might not play a major role in coloration [36]. Our study results showed that the white petal was due to the significant accumulation of flavonols and that the key factor of shades of pink was the accumulation of anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…However, the function was limited to flavonols, as a co-pigmentation, to change the petal color from magenta to blue color [34, 35]. Du et al (2018) reported the anthocyanin composition of 30 Rhododendron species and showed that there was no significant difference in co-pigmentation index among color different groups and flavonols might not play a major role in coloration [36]. Our study results showed that the white petal was due to the significant accumulation of flavonols and that the key factor of shades of pink was the accumulation of anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…'Shiro-ryūkyū' contained only flavonol. Recent research also confirmed that no anthocyanins were detected in white flowers of five wild species, including R. mucronatum (Du et al, 2018). Hirado cultivar groups were divided into four pigment groups: 1) Cy-derivatives only without flavonol, 2) Cy-derivatives and flavonol, 3) Cy-and Dpderivatives and flavonol, and 4) flavonol only.…”
Section: Discussionmentioning
confidence: 82%
“…Anthocyanins are dominant pigments that give plants the color of red, purple and purple pink. The pigmentation of flowers is determined by the type and amount of anthocyanin in the contents of the flower (7). When lingonberry (Vaccinium vitis-idaea) which is grown in Poland and blueberries (Vaccinium myrtillus L.) are compared in terms of phenolic ingredients they contain, blueberries have shown more antioxidant activity.…”
Section: D)mentioning
confidence: 99%